Stakeholder engagement from problem analysis to implementation strategies for a patient‐reported experience measure in disability care: A qualitative study on the process and experiences - Marjolein vanRooijen; Stephanie Lenzen; Ruth Dalemans; Anna Beurskens; Albine Moser (Wiley, 2021)
Abstract Background In implementation science, vast gaps exist between theoretical and practical knowledge. These gaps prevail in the process of getting from problem analysis to selecting implementation strategies while engaging stakeholders including care users. Objective To describe a process of how to get from problem analysis to strategy selection, how to engage stakeholders, and to provide insights into stakeholders' experiences. Design A qualitative descriptive design. Setting and participants The setting was a care organization providing long‐term care to people with acquired brain injuries who are communication vulnerable. Fourteen stakeholders (care users, professionals and researchers) participated. Data were collected by a document review, five interviews and one focus group. Inductive content analysis and deductive framework analysis were applied. Intervention Stakeholder engagement. Main outcome measures A three‐step process model and stakeholders experiences. Results and conclusion We formulated a three‐step process: (a) reaching consensus and prioritizing barriers; (b) categorizing the prioritized barriers and idealization; and (c) composing strategies. Two subthemes continuously played a role in how stakeholders were engaged during the process: communication supportive strategies and continuous contact. The experiences of stakeholder participation resulted in the following themes: stakeholders and their roles, use of co‐creation methods and communication supportive strategies, building relationships, stimulus of stakeholders to engage, sharing power, empowerment of stakeholders, feeling a shared responsibility and learning from one another. We conclude that the inclusion of communication‐vulnerable care users is possible if meetings are prepared, communication‐friendly presentations and reports are used, and relationship building is prioritized.